Społeczny wymiar funkcjonowania rodziny i kobiety w środowisku wiejskim - Zajdel, Krzysztof (Karkonoska Państwowa Szkoła Wyższa, 2011)
The woman's part is subject of my study and the country family in Poland in period of alternatively. Yet to recent, country family more considerably often than municipal she was numerous, and so with many children and many generations. She was perceived as more durable, less subject on divorces and separations. Beyond this nation in the country more seldom than they in city live in informal relationships, extramarital. It was can so - peaceably with social picture - at least in this field recognise the occupants of village not only za more tradycjonalnych, but and more moral. First of all however living in the country men be perceived by Poles' totality as more religious than occupants cities and it turns out, that they are tray really.
Keywords: kobieta; rodzina; środowisko wiejskie